The Legal Framework of Administrative Authority in Acceleration Committees - Abdul Karim Saleh, Researcher. Mohammed; Majeed Jassim, Assist .Prof. Batoul (Basra studies journal, 2025)
Acceleration committees represent a form of sanction for breaches of governmental contracts. Government entities possess the authority to impose such measures when a contractor fails to fulfill their contractual obligations. These committees thus constitute a type of compulsory specific performance, whereby the government authority assumes the role of executor through its technical staff, while the defaulting contractor acts as a supervisor over the execution process, since the implementation is carried out at their expense. This mechanism is grounded in legislative authority and is considered part of public order due to its inherent connection to the functioning of public services.